Segmental Structure of the Brassica napus Genome Based on Comparative Analysis With Arabidopsis thaliana - Parkin, Isobel A. P. (Copyright © 2005 by the Genetics Society of America, 2005)
Over 1000 genetically linked RFLP loci in Brassica napus were mapped to homologous positions in the Arabidopsis genome on the basis of sequence similarity. Blocks of genetically linked loci in B. napus frequently corresponded to physically linked markers in Arabidopsis. This comparative analysis allowed the identification of a minimum of 21 conserved genomic units within the Arabidopsis genome, which can be duplicated and rearranged to generate the present-day B. napus genome. The conserved regions extended over lengths as great as 50 cM in the B. napus genetic map, equivalent to ∼9 Mb of contiguous sequence in the Arabidopsis genome. There was also evidence for conservation of chromosome landmarks, particularly centromeric regions, between the two species. The observed segmental structure of the Brassica genome strongly suggests that the extant Brassica diploid species evolved from a hexaploid ancestor. The comparative map assists in exploiting the Arabidopsis genomic sequence for marker and candidate gene identification within the larger, intractable genomes of the Brassica polyploids.